Exploring the Incidence of Enterococcus faecalis in some Clinical Specimens - Hussien, Shurooq Sabah; Hussein, Alyaa R. (Iraqi Journal of Science, 2025)
Enterococci are a significant cause of hospital-acquired infections and have emerged as a global public health issue. This study aimed to assess the prevalence and characteristics of Enterococcus faecalis in local clinical samples, as well as to examine their biofilm-forming potential and antibiotic susceptibility profiles. Samples were collected from Medical City Hospitals in Baghdad city from November 2023 to February 2024. E. faecalis bacterium was isolated and identified from 120 clinical samples (tooth canal, blood, tissue and urine samples) through biochemical tests, with confirmation using Vitek 2 system. The total percentage of isolation for E. faecalis was 54.16% where 16.7% of tooth root canal and 50% of urine samples were E. faecalis positive. A total of 65 E. faecalis isolates were then studied for their capability to form biofilm using the microtiter plate method. The percentage of biofilm formation among E. faecalis clinical isolates was 1.5% non-adherent, 29.2% weak, 67.7 % moderate, and 1.5% strong. Antibiotic sensitivity testing of E. faecalis isolates from clinical samples was conducted using VITEK 2 compact system, the results showed that 100% of the isolates were resistant to Erythromycine and (95%) of the isolates were resistant to Tetracyclin, and Linezolid, while 95.40% of E. faecalis isolates were sensitive to tigecycline. showed that E. faecalis scored highest resistance toward erythromycin (100%) followed by tetracyclin (95.4%) compared to other antibiotics with significant differences (p<0.05). Additionally, present findings showed E. faecalis scored the highest sensitivity to tigecyclin (95.4%), followed by nitrofurantoin (92.3%), levofloxacin (92.3%), and then linezolid (64.6%) compared to other antibiotics with significant different (p<0.05). The biofilm production assay showed that most E. faecalis isolates produce weak and moderate biofilm (29.2% and 67.7%) respectively, and most of these bacteria were isolated from urine (80.0%) with significant differences (p<0.05) and isolated from root and tissue produce moderate biofilm (87.5% and 100%) with significant difference (p<0.05). In conclusion, our results indicate a high prevalence of E. faecalis contamination in local clinical samples, with varying abilities to produce biofilms and highlight distinct profiles for antibiotic susceptibility among the isolates.